Pengamatan IP Cycling Pada VPN Menggunakan GRC Fingerprints dan DNSLeakTest - R. Agastya Ardhitaputera Ramadhan; Justinus Andjarwirawan; Agustinus Noertjahyana (Universitas Kristen Petra, 2022)
As information technology has evolved within the modern era, the needs of information rises along with it. Where every individual need information quickly and accurately, a supporting medium must support it. One of these medium is fast internet. Many are paranoid towards the idea of the government stealing their private information and using it for what they see fit. The objective of this research is to determine whether or not the stability of said VPN is of acceptable levels. The data will be taken hour-by-hour for 30(thirty) days from www.dnsleaktest.com and www.grc.com/fingerprints.htm. The results will then be forwarded to the Google Sheets website that has been programmed to receive the IP, Hostname, ISP and Country tags from the source code from said page. Commercial VPNs are private networks that allow its users to appear to be connecting from another network. This is however not without risk, for those services may not be safe. In this experiment, we have concluded that some VPNs are unstable when used at certain times.